The fate of an oil spill in São Sebastião channel: a case study (Brazilian Journal of Oceanography, 2013)
An oil pipeline ruptured in May 1994 and 2 700 tons of crude oil leaked into the São Sebastião Channel, affecting several neighboring areas. A program for the monitoring of hydrocarbons in sediments, using the gas chromatography / flame ionization detector methodology, was being undertaken in the area at the time. The data obtained were compared to those of samples collected after the accident to determine the fate of the oil spilled and ascertain its contribution to the environment. The earlier results showed that hydrocarbons were introduced from two different sources: biogenic, mainly from terrestrial plants, and anthropogenic, as oil, in sewage and from shipping. The later data indicated that the site closest to the pipeline rupture had been the most affected. Following that, two stations located at the north entrance of the channel presented the highest n-alkane concentrations, suggesting that the northeasterly wind-driven currents had carried the oil northward. Seven months later, one of these stations, a high-energy site, showed some signs of recovery, but this process was not observed at the other, which seemed to be a low-energy site. In conclusion, the data showed that the aliphatic hydrocarbon analyses were powerful tools for the assessment of the fate of the oil spill and that the northern part of the São Sebastião Channel is more subject to the effects of oil spills.